Bridging Ethical and Anti‐Ethical Norms: A Framework for Enhancing Renewable Energy Investment in Indonesia - Kurniawan, Ova; Triandi, Adrian Ova; Susetyo, Ferry Budhi (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
This paper examines the interplay between ethical norms and anti‐ethical norms in shaping investment decisions within Indonesia’s renewable energy sector. Drawing on Mertonian ethical norms as a theoretical backbone and contrasting them with non‐market strategy perspectives, the study reviews how business ethics intersect with renewable energy policy, investment, and sustainable development in Indonesia. Using recent data from national energy statistics and empirical studies on renewable energy and ESG disclosure , the paper develops a research framework. By combining institutional theory and stakeholder theory, this study uses a theory-driven conceptual qualitative approach to provide a normative-analytical framework that clarifies how ethical standards and non-market tactics influence Indonesia's investment in renewable energy. The framework suggests that a balanced approach—integrating both ethical imperatives and pragmatic market strategies—can drive progress toward national targets such as the Golden Indonesia 2045 vision and the Paris Agreement’s zero‐carbon goals.